Solve for happy engineer your path to joy /cMo Gawdat - Gawdat, Mo (North Star Way, 2017)
In Solve for Happy Mo questions some of the most fundamental aspects of our existence, shares the underlying reasons for suffering, and plots out a step-by-step process for achieving lifelong happiness and enduring contentment. He shows us how to view life through a clear lens, teaching us how to dispel the illusions that cloud our thinking; overcome the brain's blind spots; and embrace five ultimate truths. No matter what obstacles we face, what burdens we bear, what trials we've experienced, we can all be content with our present situation and optimistic about the future